Spatiotemporal dynamics of multidrug resistant bacteria on intensive care unit surfaces - Alaric W. D’Souza (Nature Portfolio, 2019)
The authors investigate the burden and spatiotemporal dynamics of multidrug-resistant bacteria on intensive care unit surfaces from two hospitals in the US and Pakistan over a year. They find Acinetobacter baumannii and Enterococcus faecium co-association, likely due to synergistic biofilm formation.